Designing Futures : Speculation, Critique, Innovation - Groß, Benedikt, ....-; Mandir, Eileen, ....- (London : Laurence King, 2024)
The ability to imagine different possible futures and the will to influence the course of events are deeply human. These ideas about the future can also determine which of the many possible futures will become reality. Designing futures therefore means that by creating and communicating potential scenarios, you can shape the futures of your fellow human beings and influence the course of events. Design is becoming more strategic as a discipline, moving away from 'making things beautiful' to 'thinking creatively'. This book provides designers with the methods and tools they need to develop discussable and tangible scenarios. It also outlines ways for creative people, activists and decision-makers in politics, science and the wider society to imagine more desirable futures.
Keywords: Design; Future; Toekomst